High prevalence of ST131 among CTX-M-producing Escherichia coli from community-acquired infections, in the Czech Republic - Papagiannitsis, Costas C; Študentová, Vendula; Jakubů, Vladislav; Španělová, Petra; Urbášková, Pavla; Žemličková, Helena; Hrabák, Jaroslav (Microbial drug resistance (Larchmont, N.Y.), 2015)
A total of 2,683 nonrepetitive Escherichia coli isolates were collected from microbiological laboratories covering all regions of the Czech Republic, during April 2011. Antimicrobial susceptibility patterns of E. coli were assessed. All 38 cefotaxime-resistant (CTX-R) isolates were found to be extended-spectrum β-lactamase (ESBL)-positive by the double-disc synergy test. Thirty-two of those isolates produced enzymes of CTX-M-1 family, five of CTX-M-9 family, and one isolate both CTX-M types. Genotyping by multilocus sequence typing classified all ESBL-producing isolates into 13 sequence types (STs). ST131 was the most prevalent and was exclusively correlated with E. coli belonging to the more-virulent phylogroup B2. blaCTX-M-15 and blaCTX-M-9-like genes were mainly carried by plasmids belonging to the IncF group, while replicon I1 was predominant among CTX-M-1-encoding plasmids. Additionally, 63% of the ESBL-producing isolates were also resistant to ciprofloxacin. Sequence analysis of quinolone resistance-determining regions of gyrA and parC revealed the presence of amino acid substitutions in 22 out of 23 ciprofloxacin-resistant isolates. The acc(6')-Ib-cr and qnrB1 plasmid-mediated quinolone resistance genes were also detected in some of the isolates. This is the first report on the emergence and spread of CTX-M-producing E. coli in the community of the Czech Republic, indicating the high prevalence of ST131 clone among CTX-M producers.
Keywords: senioři; buněčné klony; Prevalence; Anti-Bacterial Agents; senioři nad 80 let; proteiny z Escherichia coli; DNA, Bacterial; Disk Diffusion Antimicrobial Tests; Male; kojenec; mladiství; Česká republika; virulence; Middle Aged; mužské pohlaví; prevalence; Infant; Adult; bakteriální geny; Czech Republic; dítě; DNA bakterií; Child; Aged, 80 and over; Child, Preschool; Multilocus Sequence Typing; konjugace genetická; Escherichia coli; ženské pohlaví; fluorochinolony; Humans; předškolní dítě; Virulence; Fluoroquinolones; fylogeneze; Plasmids; beta-laktamasy; Drug Resistance, Multiple, Bacterial; antibakteriální látky; infekce získané v komunitě; lidé středního věku; Escherichia coli Proteins; beta-Lactamases; Escherichia coli Infections; mnohočetná bakteriální léková rezistence; plazmidy; Genes, Bacterial; pulzní gelová elektroforéza; dospělí; multilokusová sekvenční typizace; Clone Cells; Aged; Electrophoresis, Gel, Pulsed-Field; Female; Adolescent; Phylogeny; Conjugation, Genetic; lidé; infekce vyvolané Escherichia coli; diskové difúzní antimikrobiální testy; Community-Acquired Infections